Variabel-Variabel Yang Mempengaruhi Ekspor Nonmigas Indonesia Ke Amerika Serikat - Pramana, Komang Amelia Sri; Meydianawath, Luh Gede (Jurnal Ekonomi Kuantitatif Terapan, 2013)
This study is aimed to determine the simultaneous and partial effect between US dollar exchange rates, foreign direct investment, lending rates and wholesale price index towards non-oil export of Indonesia to Unites States of America in the period of 1991-2011 and to determine which of the variables that has the dominant influence on Indonesia’s non-oil exports to the United States in the year 1991 to 2011. The analysis technique being used was the multiple linear regression analysis and assisted by SPSS computer application. The result of the study showed that 94,4% variables of the US dollar exchange rates, FDI, lending rates and WPI are simultaneously influence the Indonesia’s non-oil exports to the United States from 1991 to 2011, while the remaining 5.6 percent is influenced by other variables outside the model being used. Partially, the U.S. dollar exchange rate and FDI variable have the positive and significant effect, on the other hand WPI variable has the negative and significant effect towards Indonesia’s non-oil exports to the United States, whereas the lending rates has no significant impact towards Indonesia’s non-oil exports to the United States in the year 1991 to 2011, at 5 persen level of significance. The analysis also indicated that the US exchange rates variable has the most dominant influence toward the Indonesia’s non-oil exports to the United States in the year 1991 to 2011. In order to increase the surplus of Indonesia’s international trade which was represented by the value of non-oil export from Indonesia to United States of America; the commodity producers are expected to implement the changes on the current non-oil export product into the product which are more oriented into finished goods. Moreover, by referring to the result of the analysis in which the US Dollar exchange rate was the most dominant variables, the government have to impose the implementation of a policy to stabilize the Rupiah exchange rate; particularly to US Dollar.
Keywords: Non-oil Export; Exchange Rate; Foreign Direct Investment; Lending Rates; Wholesale Price Index